Autophagy and Skin Diseases - Kim Klapan; Dagmar Simon; Alexander Karaulov; Marina Gomzikova; Albert Rizvanov; Shida Yousefi; Hans-Uwe Simon; Hans-Uwe Simon; Hans-Uwe Simon; Hans-Uwe Simon (Frontiers Media S.A., 2022)
Autophagy is a highly conserved lysosomal degradation system that involves the creation of autophagosomes, which eventually fuse with lysosomes and breakdown misfolded proteins and damaged organelles with their enzymes. Autophagy is widely known for its function in cellular homeostasis under physiological and pathological settings. Defects in autophagy have been implicated in the pathophysiology of a variety of human diseases. The new line of evidence suggests that autophagy is inextricably linked to skin disorders. This review summarizes the principles behind autophagy and highlights current findings of autophagy's role in skin disorders and strategies for therapeutic modulation.